Semi-permeable polymer vesicle-based prooxidative and lactate-depleting nanoreactors with sustained activity against pancreatic cancer - Sun, Lili; Pan, Qian; Li, Yunfei; Mu, Yanxi; Cheng, Yusheng; Feng, Yeqian; Tanaka, Masaru; Wen, Panyue; Liu, Xianling (Frontiers in Bioengineering and Biotechnology, 2025)
Polymer vesicles, also known as polymersomes, consist of polymer membranes enclosing an aqueous core and have attracted significant interest for biomedical applications. The aqueous core is particularly advantageous for encapsulating and stabilizing fragile cargo, such as proteins, to maintain long-term activity. Among these, enzyme-encapsulated polymersomes function as therapeutic nanoreactors and have gained increasing attention in recent years, especially for cancer treatment. A critical factor in their catalytic performance is ensuring semipermeability of the membrane, allowing selective exchange of small-molecule substrates while maintaining stable enzyme encapsulation. However, achieving a balance between prolonged structural integrity and optimal permeability to sustain catalytic activity remains a challenge. Here, we present oxidation-sensitive polyion complex vesicles (PICsomes) encapsulating lactate oxidase as prooxidative and lactate-depleting nanoreactors. The membrane’s built-in semipermeability and crosslinked network contribute to the prolonged enzymatic activity of lactate oxidase. Notably, in response to reactive oxygen species (ROS), the nanoreactors undergo swelling, further enhancing membrane permeability to amplify enzymatic catalysis—specifically, ROS production and lactate depletion. This self-amplifying function enhances cytotoxic effects against pancreatic cancer cells. Interestingly, the prooxidative activity also induces immunogenic cell death, as evidenced by elevated levels of calreticulin and HMGB1, suggesting the potential to stimulate antitumor immunity. It is important to note that lactate not only serves as a key respiratory fuel but also facilitates immune evasion. Given these findings, the reported nanoreactors offer a promising strategy for disrupting tumor energy and redox metabolism through lactate depletion and prooxidation, while also priming antitumor immunity for combination immunotherapy.